Cities of the global South reader - Miraftab, Faranak; Kudva, Neema (Routledge urban reader series, 2015)
"The Cities of the Global South Reader adopts a fresh and critical approach to the field of urbanization in the developing world, which has seen significant shifts in its thematic and geographic focus since it first began to be defined in the mid-twentieth century. This Reader incorporates both early readings and new and emerging debates that reflect advancements in the area over the past 30 years and celebrates the diversity of the Global South. . The thematic structure and selection of texts in the Cities of the Global South Reader recognizes the dichotomies of wealth/poverty, development/underdevelopment, first/third worlds, and various forms of inclusion/exclusion. This conceptual framework shapes the Reader's organization around global processes such as colonialism and development and examines the issues and concerns that policy makers face in the contemporary world. These include the urban economy, housing, basic services, infrastructure, the role of non-state civil society based actors, planned interventions and contestations, the role of diaspora capital, the looming problem of adapting to climate change, and the increasing spectre of violence in a post 9/11 transnational world. The Cities of the Global South Reader pulls together a diverse set of readings from scholars across the world, some of which have been written specially for the volume, to provide an essential resource for a broad interdisciplinary readership at undergraduate and postgraduate levels in urban geography, urban sociology, and urban planning as well as disciplines related to international and development studies. Editorial commentaries that introduce the central issues for each theme summarize the state of the field and outline an associated bibliography"--Publisher.